Neural Correlates Related to Anxiety in Attentional Inhibition Control: an Erp Study - Seo, S.H.; Lee, Ch.K.; Yoo, S.K. (Нейрофизиология, 2014)
We investigated the effect of anxiety on attentional inhibitory control using event-related potentials (ERPs) and measuring the response time. Nineteen participants performed a multisource interference task; three-digit numbers and emotional faces were used as visual stimuli. The P100 and P300 ERP-components and response time values were used to evaluate whether ERP parameters and behavioral responses are associated with increased anxiety. Higher anxiety was associated with a longer latency and reduced amplitude of the P300 component at F3, whereas higher anxiety was associated with a shorter latency and higher amplitude of P300 at F4. The longer P300 latency at F3 was especially related to the response time to the target number with negative-expression faces as distracters.